FORAMINIFERAL ZONAL STANDARD FOR THE LOWER CARBONIFEROUSOF RUSSIA AND ITS CORRELATION WITH THE CONODONT ZONATION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
This paper describes the zonal subdivisions of the revised Foraminiferal Scale of Russia and their correlation to conodont zones and age-equivalent beds in Western Europe and North America. The foraminiferal zonal sequence is documented in key sections and wells that cover the entire Lower Carboniferous. Boundary reference sections are proposed for most Tournaisian and Serpukhovian zones. Major evolutionary trends within the foraminifers are used to define individual zones.